2010
DOI: 10.1007/s10532-010-9334-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of diclofenac and mefenamic acid by the white rot fungus Phanerochaete sordida YK-624 and identification of their metabolites after fungal transformation

Abstract: The non-steroidal anti-inflammatory drugs diclofenac (DCF) and mefenamic acid (MFA) were treated with the white rot fungus Phanerochaete sordida YK-624. DCF completely disappeared and MFA decreased by about 90% after 6 days of treatment. It was also confirmed that the fungus almost completely removed the acute lethal toxicity of DCF and MFA towards the freshwater crustacean Thamnocephalus platyurus after 6 days of treatment. Mass spectrometric and (1)H nuclear magnetic resonance analyses demonstrated that two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 37 publications
4
53
0
4
Order By: Relevance
“…Furthermore, intracellular enzymes, such as the cytochrome P450 enzyme system of fungus, are also reported to be helpful for TrOCs removal (Golan-Rozen et al, 2011), especially, in the context of this study, for diclofenac (Hata et al, 2010).…”
Section: Enzymatic Activity and Troc Removalmentioning
confidence: 81%
“…Furthermore, intracellular enzymes, such as the cytochrome P450 enzyme system of fungus, are also reported to be helpful for TrOCs removal (Golan-Rozen et al, 2011), especially, in the context of this study, for diclofenac (Hata et al, 2010).…”
Section: Enzymatic Activity and Troc Removalmentioning
confidence: 81%
“…In a study using an ex vivo intestinal model, metabolism inhibitors increased DIC toxicity, and also reduced the generated amount of 4'-OH-DIC, 5-OH-DIC (Niu et al, 2015). Oxydative biotransformation of DIC and MEF also reduced the toxicity against a freshwater crustacean in (Hata et al, 2010). In contrast, during the metabolism of IBU into 1,2-dihydroxy-IBU by Trametes versicolor, increase in toxicity was observed in Microtox bioassay (Marco-Urrea et al, 2009b).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown the oxidative modification of these drugs. Production of 4',5-dihydroxy-diclofenac, 4',-hydroxy-diclofenac and 5-hydroxy-diclofenac from the NSAID diclofenac by Phanerochaete sordida was reported by (Hata et al, 2010). The same fungus was shown to successfully metabolize mefenamic acid into several oxidized products, like 3-OH-mefenamic acid and 3-COOH-mefenamic acid (Hata et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a recent study by Hata et al, (2010) it was found that degradation of diclofenac and mefenamic acid by white rot fungal culture may be involved in the…”
Section: Degradation Of Selected Phacs By Whole Fungal Culturementioning
confidence: 99%